Service quality measurement : issues and perspectives - Rodrigues, L. L. R. (Anchor Academic Pub., 2013)
Hauptbeschreibung This book is very useful for it is not just 'descriptive' in its nature, but 'prescriptive', too. It is descriptive in the sense that it describes the process of developing or using a metric in a problem situation, and prescriptive as it clearly prescribes how a beginner can put the theory into practice. In this globalized economy, maintaining quality of products and services has been the thrust area of interest among academicians and practitioners. Today, there are quite a good number of books and research articles available. Nevertheless, service quality meas.